Optimizing Language Learning with Relevant and Contextual Vocabulary Selection in Education - Dana Aswadi (Departement of Mathematics Education, 2024)
Effective language learning requires the right approach in selecting vocabulary used in the teaching process. Selecting relevant and contextual vocabulary is the main key to optimizing students' understanding of learning materials. Students' understanding and language skills can significantly improve with the use of relevant vocabulary that relates to their daily lives and contextual vocabulary that is appropriate for the situation or topic under discussion. This study aims to explore how choosing the right vocabulary can optimize language learning at various levels of education. The results show that choosing vocabulary that is relevant to students' social and cultural experiences, as well as vocabulary that is appropriate to the learning context, can deepen students' understanding and improve their language skills. At the elementary, secondary, and tertiary levels, the relevance and contextuality of vocabulary affect the way students relate learning materials to their real lives, so that learning becomes more meaningful. Furthermore, this study highlights the difficulties in choosing suitable vocabulary and emphasizes the need for teachers to receive training in adapting learning materials that link vocabulary to wider social, cultural, and academic contexts.